Research on the Fragmented Learning of "Java Language Programming" in the Internet + Era - Yandong, Wen (International Conference on Computer Science & Education, 2021)
Under the background of the Internet + era, the learning environment of college students has undergone earthshaking changes, and the combination of the Internet and education and teaching has also produced a new teaching model, in which Internet + fragmented learning has become the trend. The "Java Language Programming" course is a compulsory course for training Java software development engineers. This article introduces fragmentation into the teaching of this course. Through content fragmentation and time fragmentation, students ' enthusiasm for learning is greatly aroused and their personalization is satisfied The demand for learning, and finally through the mind map to achieve "recovery" and "reconstruction" of knowledge, has achieved good practical results.